Fibrous filter techniques for aerosol collection in surface engineering applications. (5th May 2009) - Rodriguez, Monica; Handy, Rod; Jackson, Mark J.; Goodman, Dave, Grant Robinson
With increased scope and activity of the nanotechnology industry, there is a need for greater understanding about filter collection performance and efficiency. Filtration is a process which is used to control the particulate fluxes in exhaust streams throughout various manufacturing and laboratory processes. Filtration becomes a key factor in effective ventilation system design, particularly in relation to environmental and health concerns. The purpose of this paper is to explore filtration theory and techniques, summarise the various filter types employed, and illustrate the effectiveness for reducing particulate emissions during the machining process.